Neural and endothelial cell-derived extracellular vesicles mediate Zika virus genome dissemination and productive infection in vivo - María-Angélica Calderón-Peláez; Myriam L. Velandia-Romero; J. Manuel Matiz-González; Jaime E. Castellanos (PLoS ONE, 2025)
Zika virus (ZIKV) is a neurotropic flavivirus linked to severe neurodevelopmental defects following prenatal exposure. While the mechanisms by which ZIKV spreads within the central nervous system remain incompletely understood, extracellular vesicles (EVs) have emerged as potential mediators of intercellular communication and viral dissemination. Here, we demonstrate that EVs derived from ZIKV-infected neural cells encapsulate full-length viral genomes capable of establishing productive in vivo infection, independent of free virions. Primary cortical neurons, astrocytes, and mouse brain microvascular endothelial cells (MBECs) from neonatal mice were infected with ZIKV at a low multiplicity of infection (MOI 0.1). EVs were isolated and treated with acid glycine buffer and RNAase to exclude residual virions or free RNA. RNA sequencing, RT-qPCR, and droplet digital PCR (dd-PCR) analyses revealed that EVs—particularly those derived from neurons and MBECs—encapsulated ZIKV RNA, including full-length viral genomes. These EVs were able to transfer viral RNA to A549 cells in vitro , and its intracranial injection into neonatal mice resulted in productive infection, confirmed by detection of ZIKV capsid protein, viral RNA, and viral antigen in brain tissue. Our findings demonstrate that EVs from ZIKV-infected neural cells can serve as vehicles for genome transfer and initiate infection, even in the absence of detectable virions. The persistence of EVs-packaged genomes post-viremia could explain clinical observations of prolonged ZIKV RNA within the nervous tissue or delayed transmission. Understanding this pathway provides new insights into ZIKV neuropathogenesis and opens potential avenues for therapeutic intervention, for example targeting EVs biogenesis or cargo sorting.